Cultural elements’ influence on visual preferences in urban waterfronts’ walkways in Malaysia - Liu, Tun; Mohd Yunos, Mohd Yazid; Muthuveeran, Adam Aruldewan S.; Mundher, Riyadh; Ismail, Nor Atiah (Frontiers in Built Environment, 2024)
With the rapid urbanization in Malaysia, human activities have caused damage to many waterfront areas. Efforts are being made to restore the connection between the community and river waterfronts while creating attractive urban spaces. However, the implementation of modern design development strategies without sufficient consideration of cultural aspects and societal visual preferences has raised a number of questions with regard to the public’s acceptance and appreciation of the newly implemented urban facades. This study aims to comprehensively examine the relationship between cultural elements and visual preferences in the context of urban waterfront walkways in Malaysia. This study implemented a photo survey to assess the visual preferences of the study’s respondents. The results indicated a significant correlation between subjects’ visual preferences and their cultural backgrounds. Additionally, the analysis of the collected data highlights a strong correlation between the presence of green elements and what the respondents perceived as part of the Malaysian culture. Additionally, the historical character of the study area, as represented by historical buildings, significantly influences the preferences of Malaysian respondents. Furthermore, certain elements, such as food carts, high-rise buildings, and water, are among the least preferred compared to other elements. Ultimately, incorporating these elements in the early design stages can contribute to the creation of culturally connected and visually appealing urban waterfront spaces in Malaysia.